A mobile solution for savings by the youth in Kenya - Mbuthia, Benson Njuguna (Strathmore University, 2016)
Kenya as a country has a poor financial savings culture as compared to its East African neighbours. Kenya is consumption driven and a majority of the people especially the youth aged 18 to 25 years lack control in their spending. The youth are not frequent savers yet their potential for saving is high as exhibited by their high expenditures on airtime. The existing saving systems in Kenya have failed to take advantage of the evident financial power of the youth, by failing to design products that entice them to frequently save. These existing systems are not individually tailored to address the saving needs of the youth in terms of convenience, appeal and familiarity. Based on the aforementioned challenges, this dissertation proposes a mobile based solution tailored for the youth to encourage frequent savings. The solution leverages on the high airtime expenditures by the youth, to bring about a savings model. The solution comprises of a mobile application that can automatically deduct airtime from the youth’s airtime account as well as deduct airtime from their parents’ or sponsors’ airtime accounts and transfer the deductions as savings for the youth in an airtime savings account. The youth can later withdraw the airtime savings in form of either airtime or money after a maturity period. The solution is based on Evolutionary Prototyping software methodology. The proposed system recorded impressive results in terms of functionality. Over 90 % of the respondents established that the accuracy, responsiveness, scalability, robustness and usability of the application range from moderate to extremely high. It is important to note that if the system is widely adopted in the country, the economic status of the youth as well as the country will be elevated.
Submitted in partial fulfillment of the requirements for the Degree of Master of Science in Mobile Telecommunications and Innovation (MSc. MTI)
Keywords: Mobile solution; Savings; Youth; Kenya; Airtime; Convenience; Appeal; Familiarity